Acculturation strategies used by unskilled migrant workers in South Korea. Issue 9 (15th July 2018) - Kim, Hyun-Jeong; Choi, Hee-Jeoung; Lee, Kyung-Won; Li, Gyeong-Min
ABSTRACT: The purpose of this study is to identify types of adaptation strategies used by unskilled migrant workers living in South Korea as they acculturated to life in the country and to determine specific characteristics by acculturation patterns. To this end, a Q methodology was used. A total of fifty-nine statements were drawn through in-depth interviews with eight migrant workers and two South Koreans working in related organizations as well as from thirteen other studies, and four factor types of acculturation patterns were identified by conducting a Q sorting on thirty-eight subjects. Interpretation of the study revealed that the subjects used four types of adaptation strategies: accepted separation, compromising integration, conflict marginalization, and harmonious assimilation. The subjects in each type showed concrete socio-psychological adaptation strategies in response to South Korea's unique culture and policies of discriminative exclusion.